Model Peningkatan Produktivitas Pertanian Berbasis Kelembagaan - Rosiana, Devy Surya; Agustin, Hesti; Wijaya, Hafidh Al Fathan; Kurniawan, Dimas Said; Utomo, Brilian Setyo (Jurnal Maksipreneur, 2025)
This research aims to develop an agricultural institutional model to support agricultural productivity in Girirejo Village. The problems faced in the agricultural sector of Girirejo Village are agricultural productivity, which is still not optimal, and the 55 lack of interest of the younger generation in the agricultural industry. Apart from that, farmers still have problems in obtaining capital and a lack of available infrastructure, and farmers are still unable to utilize technology to support agricultural activities. This research is descriptive qualitative research using the Pentahelix method. Pentahelix is ​​a model that can encourage economic growth in achieving innovation through mutually beneficial collaboration and cooperation between academics, non-governmental organizations, government, media, and industry. Institutionalization of the young farmer group is a source of information and helps human resources understand more about agricultural technology, so that it can increase agricultural productivity and the economy of the Girirejo Village community.